Test–Retest Reliability of the Effects of Continuous Theta-Burst Stimulation - Jannati, Ali; Fried, Peter J.; Block, Gabrielle; Oberman, Lindsay M.; Rotenberg, Alexander; Pascual-Leone, Alvaro (Frontiers in Neuroscience, 2019)
Objectives The utility of continuous theta-burst stimulation (cTBS) as index of cortical plasticity is limited by inadequate characterization of its test–retest reliability. We thus evaluated the reliability of cTBS aftereffects, and explored the roles of age and common single-nucleotide polymorphisms in the brain-derived neurotrophic factor (BDNF) and apolipoprotein E (APOE) genes. Methods Twenty-eight healthy adults (age range 21–65) underwent two identical cTBS sessions (median interval = 9.5 days) targeting the motor cortex. Intraclass correlation coefficients (ICCs) of the log-transformed, baseline-corrected amplitude of motor evoked potentials (ΔMEP) at 5–60 min post-cTBS (T5–T60) were calculated. Adjusted effect sizes for cTBS aftereffects were then calculated by taking into account the reliability of each cTBS measure. Results ΔMEP at T50 was the most-reliable cTBS measure in the whole sample (ICC = 0.53). Area under-the-curve (AUC) of ΔMEPs was most reliable when calculated over the full 60 min post-cTBS (ICC = 0.40). cTBS measures were substantially more reliable in younger participants (< 35 years) and in those with BDNF Val66Val and APOE ε4– genotypes. Conclusion cTBS aftereffects are most reliable when assessed 50 min post-cTBS, or when cumulative ΔMEP measures are calculated over 30–60 min post-cTBS. Reliability of cTBS aftereffects is influenced by age, and BDNF and APOE polymorphisms. Reliability coefficients are used to adjust effect-size calculations for interpretation and planning of cTBS studies.